Hair Modeling And Artistic Decoration - Rizaueva Rubiua Abduqahhor Qizi (Zien Journals, 2023)
This article describes the creative process of creating an artistic image using hairstyles, makeup, artistic and technological innovations.
Keywords: fashion designer; modeling; fashion designer-hairdresser